Hubungan Pemberian ASI Eksklusif Terhadap Pertumbuhan Pada Bayi 7-12 Bulan di Klinik Al-Fatih Medika Karawang Timur Tahun 2024 - Roberta Desi Ratnasari; Wiwin Widyastuti (Jurnal Ners, 2025)
Breast milk for infants is not just about fulfilling their nutritional needs, but also an investment for a very beneficial future. Efforts to provide breast milk to infants are made by mothers, ensuring the smooth flow of milk. Therefore, factors that can affect the milk supply in postpartum mothers must be considered, such as the mother's knowledge, anxiety levels, breastfeeding positions, and spousal support.To analyze the relationship between exclusive breastfeeding and the growth of infants aged 7-12 months at Al-Fatih Medika Clinic, Karawang Timur, in 2024.This study used a quantitative method with a cross-sectional design. Quantitative data were collected through primary data gathering via anthropometric measurements (weight and height) of the infants, along with a questionnaire on breastfeeding. To determine the relationship between independent and dependent variables, the data were analyzed using the chi-square statistical test.There were 26 underweight infants, accounting for 37.7%, and 43 infants with normal growth, making up 62.3%. There were 43 infants who received exclusive breastfeeding, representing 62.3%, while 26 infants did not receive exclusive breastfeeding, comprising 37.7%. A significant relationship was found between breastfeeding and infant growth, with a p-value of 0.000 (< 0.05).Exclusive breastfeeding has a significant impact on infant growth.